Acoustic monitoring reveals diversity and surprising dynamics in tropical freshwater soundscapes. (25th March 2018) - Gottesman, Benjamin L.; Francomano, Dante; Zhao, Zhao; Bellisario, Kristen; Ghadiri, Maryam; Broadhead, Taylor; Gasc, Amandine; Pijanowski, Bryan C.
Abstract: Freshwater systems are globally threatened and in need of enhanced monitoring and assessment. We applied soundscape recording and analysis—which presents an opportunity for long‐term, high‐resolution animal community monitoring and assessment—to a freshwater context to better understand the acoustic diversity and dynamics of these systems. We recorded the aquatic soundscape of a Neotropical freshwater swamp in Costa Rica for 23 days in January and February 2015 during the dry season. We classified biological sound types in these recordings and developed measurements of richness and occupancy based on this classification. We also calculated six complementary acoustic indices to assess soundscape diversity and daily and longer‐term soundscape dynamics, and we examined correlations between these acoustic indices and sound type metrics. We found rich soundscapes in which biological sounds were almost always present, and we classified 18 sound types that we attribute to aquatic insects. These sound types showed distinct daily patterns and exhibited temporal and spectral acoustic niche partitioning. Sound type richness was most correlated with the number of peaks index (correlation = .36; p  < .001), while sound type occupancy was most correlated with the Bioacoustic Index (correlation = .92; p  < .001). In contrast to generally high levels of acoustic activity, there were brief (approximately 1 hr), unexpected quiet periods around dawn and dusk. This study represents an early attempt to comprehensively describe tropical freshwater soundscapes in a systematic and quantitative manner. We demonstrate that sound type classification and the quantification of acoustic occupancy capture aspects of soundscape diversity and dynamics that are complementary to those assessed by acoustic indices. Our analyses reveal that the soundscapes of this tropical wetland were diverse and exhibited daily dynamics that differed from those found in other ecosystems.